Analisis Maqasid Syariah Terhadap Implementasi Penyaluran Dan Penghimpunan Dana Ziswaf Pada Lembaga Amil Zakat Baitulmal Tazkia: Sharia Maqasid - Yunita, Putri (Universitas Muhammadiyah Surabaya, 2024)
The purpose of the “Sharia Maqasid Analysis of Implementation of Channelling and Collecting of Ziswaf Funds on the Baitulmal Zakat Amil Institution of Tazkia” is to examine the extent to which the implementation of the Zakat, Infaq, Sedekah, and Wakaf (ZISWAF) fund allocation and collection of Zakat Fund has met the purpose of Shariah. The purpose of Shariah in the context of zakat is to realize the well-being of society, both materially and spiritually. This can be done through the allocation of zakat funds to eight asnaf. The channeling and disposal of ZISWAF funds must be transparent, accountable, and can also be done in a way that is easy and affordable to the public. The results of this paper are expected to provide useful information for the Amil Zakat Baitulmal Tazkia Institute in improving the quality of implementation of ZISWAF distribution and fund-raising. This paper is expected to contribute to the development of science and practice of zakat management in Indonesia. The research applies a qualitative approach as well as combines the analysis of formal literature to meet the criteria as a library research. Data sources in this research come from relevant books, journal articles, relevant academic materials, and other supporting documents. This research will explain and test secondary data based on the practices of Maqasid al-Syariah in Zakat, infak, sedekah, and wakaf. Economic Empowerment of the people of LAZ BMT channels ZISWAF funds for the people's economic empowerment programmes, such as the enterprise capital aid program, the business support program, and the entrepreneurship training program. These programmes are aimed at improving the income and well-being of the population. Improving the quality of education LAZ BMT channels ZISWAF funds for education quality improvement programmes, such as scholarship programs, education cost assistance programs, and educational facilities and facilities development programmes. These programmes aim to improve the quality of human resources. The Sharia Maqasid analysis of the implementation of ZISWAF funding and fund-raising by the Tazkia Baitulmal Institution covers principles such as justice, balance, benefits, and sustainability, which are essential in managing ZISwaF funds. Effective implementation can contribute to the empowerment of communities and social well-being. The journal also highlights the importance of coordinating the allocation of funds with Sharia Maqasid and provides examples of such implementation.